2007
DOI: 10.1073/pnas.0705186104
|View full text |Cite
|
Sign up to set email alerts
|

Structural modules for receptor dimerization in the S -locus receptor kinase extracellular domain

Abstract: The highly polymorphic S-locus receptor kinase (SRK) is the stigma determinant of specificity in the self-incompatibility response of the Brassicaceae. SRK spans the plasma membrane of stigma epidermal cells, and it is activated in an allele-specific manner on binding of its extracellular region (eSRK) to its cognate pollen coat-localized S-locus cysteine-rich (SCR) ligand. SRK, like several other receptor kinases, forms dimers in the absence of ligand. To identify domains in SRK that mediate ligand-independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
113
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 39 publications
2
113
0
2
Order By: Relevance
“…The configuration of the β-strands in both of these domains has an approximate three-fold internal symmetry, forming a "Y" or trefoil-shaped structure. As previously predicted [17], a database search using the DALI server revealed that these two lectin domains share appreciable structural similarity to a mannose-recognizing lectin from Japanese Marasmius oreades [24] despite their weak sequence similarity to the latter lectin ( Figure 2B and Supplementary information, Figure S1A). However, the hairpin loops of these proteins vary greatly in length, sequence, and conformation ( Figure 2B and Supplementary information, Figure S1A).…”
Section: The S-domain Architecture Of Esrk9mentioning
confidence: 82%
See 3 more Smart Citations
“…The configuration of the β-strands in both of these domains has an approximate three-fold internal symmetry, forming a "Y" or trefoil-shaped structure. As previously predicted [17], a database search using the DALI server revealed that these two lectin domains share appreciable structural similarity to a mannose-recognizing lectin from Japanese Marasmius oreades [24] despite their weak sequence similarity to the latter lectin ( Figure 2B and Supplementary information, Figure S1A). However, the hairpin loops of these proteins vary greatly in length, sequence, and conformation ( Figure 2B and Supplementary information, Figure S1A).…”
Section: The S-domain Architecture Of Esrk9mentioning
confidence: 82%
“…A modeling study had suggested that residues 293-346 of eSRK6 encode an EGF-like domain [17] that is principally defined by six cysteines, which are known to form disulphide bonds in a 1-3, 2-4, and 5-6 pattern [25]. Indeed, this region of eSRK9 forms a structure that can be largely aligned with that of EGF [26] ( Figure 2C).…”
Section: The S-domain Architecture Of Esrk9mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, an artifi cially expressed dimerized form of eSRK exhibited high-affi nity binding to SP11. Another recent study suggested that two regions in the extracellular domain of SRK mediated the homo-dimerization of eSRK (Naithani et al 2007 ). Taken together, these studies suggested that SRK on the stigmatic membrane is in an equilibrium between the inactive monomeric or dimeric low-affi nity forms and the dimeric active high-affi nity form, and that the SP11/SCR binding to its cognate SRK stabilizes its dimeric active form, which is expected to trigger the SI responses in the papilla cell (Shimosato et al 2009 ) (Fig.…”
Section: Self/non-self Recognition System In the Brassicaceaementioning
confidence: 99%